Developing Control Operations for Information Risk Management by Formulating a Stochastic Model (Journal of Informatics and Mathematical Sciences, 2020)
Stochastic models are becoming increasingly useful for understanding or making performance evaluation of systems arising in various scientific and engineering disciplines. The present paper is mainly devoted to the explicit formulation, the theoretical investigation, and the practical interpretation of a stochastic model having the necessary advantages for the precise description and the thorough investigation of the behavior and performance of a system evolving in the environment of a random number of competing, global, and catastrophic risks. In addition, such a system incorporates its principal concepts for the strong enforcement of the crucial requirements substantially facilitating the effective use of the formulated stochastic model to the reliable development and successful implementation of vital strategic processes.
Keywords: System; Stochastic model; Risk; Requirements; Information; Strategic process